Le giardiniere. Semi, radici, propaggini dall Inghilterra al mondo - Orestano, Francesca; Rudelli, Anna; Zappatini, Anna; Orestano, Francesca; Rudelli, Anna; Zappatini, Anna (Milan Milano University Press)
Gardeners are all those women who, from the eighteenth century to the present day, have worked in the garden, planting, pruning, selecting, illustrating, and becoming involved in the production of gardening texts, scientific and botanical research, the design of green spaces, and movements for the protection of the landscape. From England, where the passion for horticulture has a well-documented history, women protagonists in the history of the garden have travelled to America, Australia, New Zealand and Asia, crossing the borders of our old world but always carrying with them their roots, replanted in distant lands. Francesca Orestano, Anna Rudelli and Anna Zappatini have outlined these adventurous stories, and the lessons that can be learnt from them, even by growing a simple geranium on the window sill.
Le giardiniere sono tutte quelle donne che, dal Settecento ad oggi, hanno lavorato in giardino, piantando, potando, selezionando, illustrando, ed entrando nella produzione di testi sul giardinaggio, nella ricerca scientifica e botanica, nella progettazione dello spazio verde, nei movimenti per la tutela del paesaggio. Dall Inghilterra, dove la passione orticola ha una sua storia ben documentata, le donne protagoniste nella storia del giardino si sono spinte verso l America, l Australia, la Nuova Zelanda, l'Asia, superando i confini del nostro vecchio mondo ma portando sempre con sé le loro radici, ripiantate in terre lontane. Francesca Orestano, Anna Rudelli e Anna Zappatini hanno tracciato queste storie avventurose, e le lezioni che se ne possono trarre, anche coltivando un semplice geranio sul davanzale della finestra.
Italian
Keywords: Gardens (descriptions, history etc); storia del giardino; giardino all'inglese; studi sul paesaggio